Effectiveness of Process-writing Approach with Middle School Children in Developing Hindi Language Compositions - Kunwar, Nidhi (JOURNAL OF INDIAN EDUCATION, 2022)
The process-writing approach provides opportunities for students to engage with the real process involved in writing. The present paper is based on a research study done with middle school children who developed compositions in Hindi language by following process-writing approach. This qualitative study involved three phases. Each phase respectively documented significant data about participant’s initial writing competency, quality of engagement with process-writing, and observed changes in children’s approach to writing.